PENGARUH AROMATERAPI LAVENDER TERHADAP NYERI DISMENOREA PADA MAHASISWI DI PESANTREN STIKES SURYA GLOBAL YOGYAKARTA - Murwani, Arita; Amry, Riza Yulina; Hikmawati, Anna Nur; M, Ani Mashunatul (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2025)
Background: Dysmenorrhea is a common issue frequently experienced by female university students, especially during menstruation, and it can negatively affect daily activities such as studying and worship. Primary dysmenorrhea occurs due to uterine contractions caused by increased levels of prostaglandins. To address this complaint, many non-pharmacological approaches are used, one of which is complementary therapy in the form of lavender aromatherapy. Lavender (Lavandula angustifolia) is known to contain active compounds such as linalool and linalyl acetate, which have analgesic properties and provide a relaxing effect through the limbic system when inhaled. This effect has the potential to reduce pain perception. Objective:This study aims to determine the effect of administering lavender aromatherapy on the intensity of dysmenorrhea pain among female students at a pesantren in Yogyakarta. Methods: This study employed a pre-experimental design with a one-group pre-post test approach. The sample consisted of 30 female students selected using purposive sampling from the total population. Pain intensity was measured using the Numeric Rating Scale (NRS) questionnaire, based on parameters ranging from mild to severe pain. Measurements were taken before the intervention (pre-test), then participants were given lavender aromatherapy by applying two drops to a tissue to be inhaled for 10 minutes. A follow-up measurement (post-test) was conducted afterward. Results: There was a decrease in the average pain scale from 5.93 (before the intervention) to 4.00 (after the intervention). Statistical analysis using a paired t-test showed a p-value of 0.000 (p < 0.05), indicating that the administration of lavender aromatherapy had a significant effect on reducing the intensity of dysmenorrhea pain. Conclusion: The administration of lavender aromatherapy was proven to significantly reduce the intensity of dysmenorrhea pain among female students at the pesantren in Yogyakarta and can therefore be recommended as a safe and easily applicable non-pharmacological alternative therapy.